2018
DOI: 10.1088/1475-7516/2018/04/056
|View full text |Cite
|
Sign up to set email alerts
|

Generalised teleparallel quintom dark energy non-minimally coupled with the scalar torsion and a boundary term

Abstract: Within this work, we propose a new generalised quintom dark energy model in the teleparallel alternative of general relativity theory, by considering a non-minimal coupling between the scalar fields of a quintom model with the scalar torsion component T and the boundary term B. In the teleparallel alternative of general relativity theory, the boundary term represents the divergence of the torsion vector, B = 2∇µT µ , and is related to the Ricci scalar R and the torsion scalar T , by the fundamental relation: R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 76 publications
0
49
0
Order By: Relevance
“…Still, there is a long route for understanding the possible astrophysical effects of modified Teleparallel theories of gravity. It might be interesting to follow a similar approach done in this paper for other Teleparallel theories, such as scalar-tensor theories [66][67][68][69][70][70][71][72][73][74][75], non-local theories [76] or theories with non-minimally couplings between matter and gravity [77]. These works will be done in forthcoming studies.…”
Section: Case 4: Ft B =mentioning
confidence: 83%
“…Still, there is a long route for understanding the possible astrophysical effects of modified Teleparallel theories of gravity. It might be interesting to follow a similar approach done in this paper for other Teleparallel theories, such as scalar-tensor theories [66][67][68][69][70][70][71][72][73][74][75], non-local theories [76] or theories with non-minimally couplings between matter and gravity [77]. These works will be done in forthcoming studies.…”
Section: Case 4: Ft B =mentioning
confidence: 83%
“…In the teleparallel setting, scalar fields have been investigated to a moderate degree, with various extensions having been investigated in the cosmological context [23][24][25][26][27][28]. Furthermore, the effects of the boundary couplings in scalar tensor theories have been discussed in various papers [25,[29][30][31][32][33][34][35][36][37][38][39][40][41]. A recent review on various studies related to dynamical analysis in different cosmological constructions can be found in [42].…”
Section: Introductionmentioning
confidence: 99%
“…First, note that the matter action functional in the Jordan frame action (43) agrees with the action functional we used in the definition (12) of the matter action; this is the reason for using the notation involving the superscript J. Further, we see that S J m depends only on the Jordan frame tetrad and matter fields, and carries no additional, explicit dependence on the scalar field besides the implicit dependence through the definition (40). This is the most important advantage and typical reason for using the Jordan frame, since also the resulting matter field equations ̟ J I = 0 are expressed in terms of the Jordan frame tetrad and matter fields only, without further dependence on the scalar field.…”
Section: A Jordan Framementioning
confidence: 56%
“…Note that in contrast to the algebraic conditions (40) and (49) for the Jordan and Einstein frame transformations we obtain a differential equation, which fixes γ D only up to an additive constant. Hence, also the corresponding debraiding tetrad θ D a = e γ D (φ) θ a is determined only up to a constant factor.…”
Section: Debraiding Framementioning
confidence: 94%